Designing a research infrastructure (RI) on food behaviour and health: Balancing user needs, business model, governance mechanisms and technology. (October 2021) - Timotijevic, L.; Astley, S.; Bogaardt, M.J.; Bucher, T.; Carr, I.; Copani, G.; de la Cueva, J.; Eftimov, T.; Finglas, P.; Hieke, S.; Hodgkins, C.E.; Koroušić Seljak, B.; et al.
Abstract: Background: A better understanding of food-related behaviour and its determinants can be achieved through harmonisation and linking of the various data-sources and knowledge platforms. Scope: We describe the key decision-making in the development of a prototype of the Determinants and Intake Platform (DI Platform), a data platform that aims to harmonise and link data on consumer food behaviour. It will be part of the Food Nutrition Health Research Infrastructure (FNH-RI) that will facilitate health, social and food sciences. Approach: The decision-making was based on the evidence of user needs and data characteristics that guided the specification of the key building blocks of the DI Platform. Eight studies were carried out, including consumer online survey; interview studies of key DI Platform stakeholders; desk research and workshops. Key findings: Consumers were most willing to share data with universities, then industry and government. Trust, risk perception and altruism predicted willingness to share. For most other stakeholders non-proprietary data was most likely to be shared. Lack of data standards, and incentives for sharing were the main barriers for sharing data among the key stakeholders. The value of various data types would hugely increase if linked with other sources. Finding the right balance between optimizing data sharing and minimizing ethical and legal risks was considered a key challenge. Conclusions: The development of DI Platform is based on careful balancing of the user, technical, business, legal and ethical requirements, following the FAIR principles and the need for financial sustainability, technical flexibility, transparency and multi-layered organisational governance. Highlights: There is a need to better support science on food intake and its determinants (DI). DI Platform links consumer, business, science-generated data on food consumption. Decision-making is based on evaluations of user needs and data characteristics. The final design balances user, technology, business and governance requirements. DI Platform supports the Food Nutrition Health Research Infrastructure initiative.